"Support for the supporters": a qualitative study of the use of WhatsApp by and for mentor mothers with HIV in the UK. Issue 2 (13th May 2020) - Hay, Kiersten; Kwardem, L.; Welbourn, A.; Namiba, A.; Tariq, S.; Coventry, L.; Dhairyawan, R.; Durrant, A.
ABSTRACT: Third-sector organizations, an important support for people living with HIV, increasingly use digital technology to improve service efficiency and reach. However, there is limited empirical evidence on this use by women living with HIV. The 4M Network (4MNet) is a peer-run UK-wide network of trained Mentor Mothers (MMs) living with HIV; it uses the WhatsApp platform as its primary digital communication tool. We report on a qualitative study about 4MNet MMs' experiences of using WhatsApp, to inform the design of future digital support services. Seven telephone interviews were conducted with five MMs and two project management team (PMT) members in February 2019. Interviews were analyzed using Interpretive Phenomenological Analysis (IPA). WhatsApp was found to have several key features that provided both positive and negative use considerations. WhatsApp eased communication among MMs and supported participation in group activities despite differing schedules and geographic locations. Challenges encountered with WhatsApp included: financial restrictions to data storage and continual access; self-confidence using technology; and security and privacy concerns. Peer-led digital communication is found to be acceptable and effective for women living with HIV. Understanding barriers and valued features of existing digital platforms increasingly used among potentially marginalized groups is vital for informing inclusive innovation.